Maize monoculture supported pre-Columbian urbanism in southwestern Amazonia - Umberto Lombardo; Lautaro Hilbert; McKenzie Bentley; Christopher Bronk Ramsey; Kate Dudgeon; Albert Gaitan-Roca; José Iriarte; Andrés G. Mejía Ramón; Sergio Quezada; Marco Raczka; Jennifer G. Watling; Eduardo Neves; et al. (Nature, 2025)
Abstract The Casarabe culture (500–1400 ce), spreading over roughly 4,500 km2 of the monumental mounds region of the Llanos de Moxos, Bolivia, is one of the clearest examples of urbanism in pre-Columbian (pre-1492 ce) Amazonia. It exhibits a four-tier hierarchical settlement pattern, with hundreds of monumental mounds interconnected by canals and causeways1,2. Despite archaeological evidence indicating that maize was cultivated by this society3, it is unknown whether it was the staple crop and which type of agricultural farming system was used to support this urban-scale society. Here, we address this issue by integration of remote sensing, field survey and microbotanical analyses, which shows that the Casarabe culture invested heavily in landscape engineering, constructing a complex system of drainage canals (to drain excess water during the rainy season) and newly documented savannah farm ponds (to retain water in the dry season). Phytolith analyses of 178 samples from 18 soil profiles in drained fields, farm ponds and forested settings record the singular and ubiquitous presence of maize (Zea mays) in pre-Columbian fields and farm ponds, and an absence of evidence for agricultural practices in the forest. Collectively, our findings show how the Casarabe culture managed the savannah landscape for intensive year-round maize monoculture that probably sustained its relatively large population. Our results have implications for how we conceive agricultural systems in Amazonia, and show an example of a Neolithic-like, grain-based agrarian economy in the Amazon.